Inhibition of checkpoint kinase 1 potentiates anticancer activity of gemcitabine in bladder cancer cells - Makoto Isono (Nature Portfolio, 2021)
Abstract Checkpoint kinases (CHKs) are involved in the DNA damage response in many cancer cells. CHK inhibitors have been used in clinical trials in combination with chemotherapeutics; however, their effect against bladder cancer remains unclear. Here, we investigated the efficacy of combining gemcitabine with MK-8776, a novel CHK1 inhibitor, in four bladder cancer cell lines. The effects of gemcitabine and MK-8776 on cell viability, clonogenicity, cell cycle, and apoptosis were examined alongside in vivo efficacy using murine xenograft tumor models. Combined treatment inhibited the viability and colony formation of bladder cancer cells compared to either single treatment. Although gemcitabine (10 nM) alone increased the cell number in S-phase, it increased the cell number in sub-G1 phase when combined with MK-8776 (0.5 µM). Combined treatment enhanced cleaved poly[ADP-ribose]-polymerase expression alongside the number of annexin-V-positive cells, indicating the induction of apoptosis. In vivo, administration of gemcitabine and MK-8776 was well tolerated and suppressed tumor growth. Mechanistically, the combined treatment elevated γH2A.X and suppressed Rad51 expression. Our study demonstrates that MK-8776 and gemcitabine combined induces apoptosis and suppresses proliferation in bladder cancer cells by inhibiting CHKs and DNA repair. Therefore, CHK1 inhibition combined with gemcitabine may be a potential treatment for bladder cancer.